Sistem Pengendalian Kamera Jarak Jauh Terintegrasi Internet Of Things - Ahzarina Safura; Andri Jabal Nur; Devi Ayu Lestari; Siti Khairiyah; David Jumpa Malem Sembiring; Meiliyani Br. Ginting (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2023)
The camera is a set of tools that aim to help human needs in the field of photo and video, today's photographers and videographers need sophisticated equipment and can help make taking pictures easier One of the benefits of this remote camera motion control system is that it functions to move the camera using a smartphone without having to be controlled manually by holding it. Based on this, an Internet of Things Integrated Remote Camera Control System will be built. This camera control system uses sensors that function to detect proximity to objects, and uses Arduino 328 as a microcontroller which functions to process input data from sensors. The test results show that the system is able to control the camera via Android at the time of retrieval of documentation as we want.